Feminist Collections, v.11, no.3 (spring 1990) - (:unkn) unknown (My University, 1990)
Subtitle: A Quarterly of Women's Studies Resources. 27p.
BOOK REVIEWS: Moving Ahead in the Academy, by Jane Ayer. Visionary Feminist Writing, by Karen Axness. Writing Our Own Lives, by Laura Zlogar. FEMINIST VISIONS: Activists, Nationalists, Feminists: The Experience of Women of Color in the U.S., by Alejandra Elenes. AN ENCYCLOPEDIC UNDERTAKING: An intervew with Helen Tierney, author of the new Women's Studies Encyclopedia. RESEARCH EXCHANGE. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES: A new bibliography on libraries and the new scholarship on gender. FEMINIST PUBLISHING: Two feminist book fairs, a lesbian/gay writers conference, two new presses, one press' audio venture, and the closing of a feminist news service. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Bibliographies on women writing about Vietnam, U.S. women artists, South American women authors, sex discrimination in education and the professions, German, Austrian, and Swiss women writers, Edith Wharton, women's issues, Julia Kristeva, and the status of women in librarianship; directories of professional and business women, women's studies programs and library resources, sexual assault services and programs, women book publishers in the U.S., and financial aids for women; plus a database on women of color and Southern women, a handbook on women's education, a work on women philosophers, a sourcebook on women explorers and travelers, a review of women's health care, a handbook on U.S. women's history, a legal guide for lesbian and gay couples, and a listing of research-in-progress. PERIODICAL NOTES: New periodicals on radical thinking, women in society, lesbian and gay studies, Emma Goldman, native women, women over forty, socialist-feminist perspectives, escaping poverty, women in prison, women workers' health in Australia, spirituality, women in the trades, the environment, and legal issues. Special issues on theater, women in conservation, Roman women, media, the Black family, and feminism in the law. Transitions: Calyx changes publication schedule; Newsletter of the Center for Research on Women, Spiritual Women's Times, and the Newsletter of the Arthur & Elizabeth Schlesinger Library on the History of Women all take on new names. ITEMS OF NOTE: A microform version of the Schlesinger Library's vertical files; the Emma Goldman Papers Project; a new book series on lesbian and gay studies; the AARP Women's Initiative; posters on sex equity and on U.S. Jewish women; and a move for WINGS news service. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews